Elif Shafak:The Voice of The Other - Nafea Al-Sammarraie, Mohammed Nihad (Opción, 2019)
This study explores one of the common problems in communities with mul- ticultural backgrounds, when minorities fall victims of the extreme practices of the majority, eventually they suffer being marginalized and treated as “the other”. It exhibits this problem as it appears in the works and interviews of the Turkish bestseller author and novelist, Elif Shafak. The study presents a brief background about the Turkish society as a multicultural one enumerat- ing the elements shaping this multicultural identity. It also relates the Turkish society with the idea of otherness. It, then, discusses this problem by referring to Shafak’s writings and interviews discussing it. It is divided into three parts, an introduction, a chapter, and a conclusion. The Introduction briefs cultural traits of the Turkish society, Shafak’s life background and a brief sketch about the idea of otherness. Whereas, the chapter discusses the problem of otherness in two of Shafak’s novels: The Bastard of Istanbul, and The Forty Rules of Love, and then present solutions through the idea of cosmopolitanism. The conclusion sums up the findings of the study.